Approaches for a semiotic analysis of the Eucharistic celebration as a pedagogical act and significant cultural practice (Encuentros, 2018)
The culture system constitutes a specific modality of learning appropriate behaviors. Religion as a socio-cultural phenomenon has great signic manifestations that generate meanings. It is intended to determine how the Celebration of the Eucharistic Liturgy is constituted as a pedagogical act and significant cultural practice. The methodological design is descriptive, based on qualitative records, in an Introspective-Experiential epistemological approach. Conclusions: The Eucharistic celebration as a communicative and pedagogical act is a cognitive semiotic process that is generated in a community of parishioners, located in an environment of production of meanings and meanings, in which only within this space is possible the realization of the action Communication and the production of new information.